Ocena polityki regionalnej Unii Europejskiej w świetle badań empirycznych - Lewandowski, Krzysztof (Gospodarka w Praktyce i Teorii, 2011)
This paper deals with controversial problem of evaluation of EU regional policy. The bulk of research concentrates on estimation how the regional policy fulfilled the most important objective of this policy - reducing the existing disparities between EU regions. That is why the most popular form of assessing the impact of regional policy became measuring the convergence. This article consists of three parts. The first one deals with the empirical research on the convergence process within the EU. The second part presents the group of research which confirmed the positive impact of EU regional policy. The last part presents the examples of works which reached the quite opposite conclusions.